Loss of Atrx Sensitizes Cells to DNA Damaging Agents through p53-Mediated Death Pathways - Conte, Damiano (Public Library of Science, 2012)
Prevalent cell death in forebrain- and Sertoli cell-specific Atrx knockout mice suggest that Atrx is important for cell survival. However, conditional ablation in other tissues is not associated with increased death indicating that diverse cell types respond differently to the loss of this chromatin remodeling protein. Here, primary macrophages isolated from Atrx (f/f) mice were infected with adenovirus expressing Cre recombinase or β-galactosidase, and assayed for cell survival under different experimental conditions. Macrophages survive without Atrx but undergo rapid apoptosis upon lipopolysaccharide (LPS) activation suggesting that chromatin reorganization in response to external stimuli is compromised. Using this system we next tested the effect of different apoptotic stimuli on cell survival. We observed that survival of Atrx-null cells were similar to wild type cells in response to serum withdrawal, anti-Fas antibody, C2 ceramide or dexamethasone treatment but were more sensitive to 5-fluorouracil (5-FU). Cell survival could be rescued by re-introducing Atrx or by removal of p53 demonstrating the cell autonomous nature of the effect and its p53-dependence. Finally, we demonstrate that multiple primary cell types (myoblasts, embryonic fibroblasts and neurospheres) were sensitive to 5-FU, cisplatin, and UV light treatment. Together, our results suggest that cells lacking Atrx are more sensitive to DNA damaging agents and that this may result in enhanced death during development when cells are at their proliferative peak. Moreover, it identifies potential treatment options for cancers associated with ATRX mutations, including glioblastoma and pancreatic neuroendocrine tumors.